ANALISA YURIDIS TENTANG PERJANJIAN DINYATAKAN BATAL DEMI HUKUM - Nanin Koeswidi Astuti (to-ra, 2016)
Judge’s decision which states that an agreement is null and void set forth in Article 1320 of the Civil Code, carry legal consequences of the agreement made by the parties, the agreement is no longer valid or has never been considered and restored to the original condition as in when the agreement has not been implemented. In practice, the judge gives the verdict declared the agreement null and void , because the requirements are not met the objective validity of a treaty that is about a particular thing and a cause that is not violate regulations.Kata Kunci: Perjanjian Batal Demi Hukum